FACTORS AFFECTING STUDYING BY TEACHER EDUCATION STUDENTS AMIDST PANDEMIC - Marshall James P. Dantic; Jhoana Marie L. Aragon (Galaxy International Interdisciplinary Research Journal, 2022)
Based from the literatures, there are numerous factors that greatly affects the studying of the students amidst pandemic. The study have used descriptively correlational research design where survey questionnaire as the main instrument in gathering data. There are 100 Teacher Education Students that served as the participants of the Study. The research instrument have two parts; profile of the participants and factors affecting their studies. The factors affecting their studies include; Personal, Teacher, Motivation to Learn and Learning Environment. Based from the results of the study, it was concluded that; most of the participants ages from 20-21, female, non-working and have a 1-3 siblings. They have a monthly family income of P10,000 and below. The participants have agreed that all the factors affects their studying amidst pandemic. There is a significant difference in the teacher, learning environment and motivation factors that affects studying when grouped according to profiles monthly family income and siblings.